Coercion in psychiatry: the importance of extramural factors - Andersen, Kjeld; Nielsen, Bent (Nordic journal of psychiatry, 2016)
Background: Mechanical restraints and forced procedures in psychiatric wards are of major concern in Denmark and there is a desire to reduce these procedures to a minimum. So far, focus has primarily been on identifying and changing internal (intramural) factors when seeking to reduce coercion. Aim: To identify possible external (extramural) factors that may increase the risk of coercion during admission to a closed psychiatric ward. Method: Using a retrospective case-controlled design, 235 patients admitted to a closed ward during 2011-2013 were randomly selected. Coercion comprised belt restraint, physical restraint, and forced medication. The data source was the electronic patient records, which include statutory information on all forced measures. Multiple logistic regression analyses were applied to calculate the risk (odds ratio, OR (95% confidence interval)) of forced measures being used. Results: Out of the 235 patients, 66 (28%) were subject to coercion. The time of forced procedures was predominately during the first hours after admission. The risk of forced measures being applied was significantly higher if patients were involuntarily admitted (OR = 6.4 (3.4-11.9)), or were acutely intoxicated by substances at the time of admission (OR = 3.7 (1.7-8.2)). Conclusion: Extramural factors should be included when mental health authorities plan efforts to reduce coercion during admission to psychiatric wards. A reduced threshold for admission and improved integrated effort between mental health services and treatment for substance abuse could improve the course of disease for this group of patients and reduce the need for involuntary admissions and subsequently coercion.